ASSESSMENT OF THE INCREASE IN THE QUANTITY OF ACTIVE INTERFERONS IN THE BLOOD OF PATIENTS WITH RECURRENT HCV WITH THE HELP OF IMMUNOCORRECTORS - Zhurayev Jamol Sirojiddinovich (Innovate Conferences, 2025)
Hepatitis C virus is the main cause of liver diseases. According to the World Health Organization, more than 50 million people are currently infected with this disease. Every year, 350,000 people die from this disease. In 95% of cases, the chronic form develops. The main complications of viral hepatitis C are liver fibrosis, liver cirrhosis and hepatocellular carcinoma [2,4,6]. We know that currently viral hepatitis C is treated with modern antiviral drugs. The effectiveness of these drugs has been demonstrated in clinical and laboratory studies. In some cases, patients with chronic viral hepatitis may experience a relapse despite treatment with antiviral drugs. There are many reasons for the relapse, and this is certainly an unpleasant event for both the patient and the treating physician [2,6].
Keywords: hepatitis C virus, relapse, interferons, InIn-immunocorrector, T-lymphocytes, immunity, immunomodulation.